SELECTION OF BITUMEN FOR THE PRODUCTION OF ASPHALT CONCRETE MIXTURES CONSIDERING THE OPERATING CONDITIONS - Alina Yunak; Ivan Kopynets; Oksana Sokolova (Дороги і мости, 2022)
Introduction. Asphalt concrete is the most common material for paving layers of roads. Significant advantages of asphalt concrete include high operational characteristics, relatively high technical values, suitability for regeneration and more. At the same time, asphalt concrete has its drawbacks, one of which is the significant dependence of strength and deformation characteristics fronm the ambient temperature. The essential role in the temperature properties of asphalt concrete is played by bitumen, the quality of which is currently evaluated by standard indicators in accordance with the penetration system. The properties of bitumen can be more accurately and objectively evaluated by rheological indicators (viscosity and cohesion) or by operational ones, which are determined depending on the climatic conditions of asphalt concrete layers. Therefore, there is a need to analyze the climatic conditions of asphalt concrete in the pavement structure.